2014
DOI: 10.1590/abd1806-4841.20142037
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of repeated episodes of type 2 reaction of leprosy with the use of thalidomide 100 mg/day

Abstract: BACKGROUNDLeprosy can have its course interrupted by type 1 and 2 reactional episodes, the last named of erythema nodosum leprosum (ENL). Thalidomide has been the medication of choice for the control of ENL episodes since 1965.OBJECTIVESThese episodes can repeat and cause damages to the patient. In order to prevent these episodes, an extra dose of 100 mg/day thalidomide was used during six months, followed by a follow-up period of six more months after thalidomide discontinuation.METHODSWe included 42 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
7
0
3
Order By: Relevance
“…Isto se deve à cronicidade e complicações da doença, com consequente limitação funcional, impacto na realização de atividades, participação social 8,9,15 e, até mesmo, na sustentabilidade econômica individual e familiar, dada a necessidade de afastamento temporário ou até mesmo permanente dos serviços em que trabalham. 38,39 O padrão de zona de moradia assemelhase ao encontrado na literatura 9,33,40 supondo que o maior número de casos residentes na zona urbana proporciona, em tese, um melhor acesso aos serviços de saúde. 15 mensal em SM e o analfabetismo são as condições socioeconômicas mais precárias se apresentam como realidade da população estudada com incapacidades físicas, ainda que com significância estatística somente para a variável renda escolaridade, se mostra compatível com pesquisas realizadas na região Nordeste brasileira 13,14,15,33,34,40 e outras realizadas na Índia e Indonésia.…”
Section: Resultsunclassified
“…Isto se deve à cronicidade e complicações da doença, com consequente limitação funcional, impacto na realização de atividades, participação social 8,9,15 e, até mesmo, na sustentabilidade econômica individual e familiar, dada a necessidade de afastamento temporário ou até mesmo permanente dos serviços em que trabalham. 38,39 O padrão de zona de moradia assemelhase ao encontrado na literatura 9,33,40 supondo que o maior número de casos residentes na zona urbana proporciona, em tese, um melhor acesso aos serviços de saúde. 15 mensal em SM e o analfabetismo são as condições socioeconômicas mais precárias se apresentam como realidade da população estudada com incapacidades físicas, ainda que com significância estatística somente para a variável renda escolaridade, se mostra compatível com pesquisas realizadas na região Nordeste brasileira 13,14,15,33,34,40 e outras realizadas na Índia e Indonésia.…”
Section: Resultsunclassified
“…Small clinical trials have shown that methotrexate administered with low-dose corticosteroids is effective and safe as a corticosteroid-sparing agent. Pentoxifylline, which inhibits tumor necrosis factor (TNF) production, has also been used to treat ENL [120][121][122][123]. Inhibitors of TNFα such as infliximab have been used in cases of severe ENL refractory to other agents [124].…”
Section: Enl (Type 2 Reactions) and Treatmentmentioning
confidence: 99%
“…Reactional episodes constitute an exacerbated inflammatory process resulting from changes in the balance between the host and M. leprae , which may occur before, during, or after the treatment of leprosy (Foss and Motta, ). There are two main types of reactional episodes: the reverse reaction (RR) or type 1, and the erythema nodosum leprosum (ENL) or type 2 (Foss et al , ; Moraes et al , ; Putinatti et al , ; Reibel et al , ). Their pathophysiological mechanisms are uncertain and are possibly associated with the inflammatory reaction related to conditions such as immunization, stress, pregnancy, puberty, childbirth, surgery, use of drugs such as antibiotics, potassium iodide, progesterone, and vitamin A, and infectious diseases, including viral or bacterial recurrent infections (Sarno et al , ; Foss et al , ; Lastoria and Abreu, ; Cortela et al , ).…”
Section: Reactional Episodes and Oral Infectionsmentioning
confidence: 99%